2017
DOI: 10.1108/oir-09-2015-0297
|View full text |Cite
|
Sign up to set email alerts
|

Misinformation in a riot: a two-step flow view

Abstract: Purpose Misinformation can have lasting impacts in the management and control of a public emergency. The purpose of this paper is to demonstrate how misinformation flows and how user characteristics can shape such flows in the context of a violent riot in Singapore. Design/methodology/approach The authors apply the two-step flow theory and discuss the mixed methods approach involving wrangling Twitter data and descriptive analysis to develop and analyse two corpuses of misinformation related to the riot. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…This four-stage rumor interaction process suggests, like other previous research (e.g. Pang and Ng, 2017), the virality of misinformation can be contingent upon the influences of users on social media platforms. Such importance of communicating actors is further supported by Qin et al (2015, p. 369) who suggest that "the individual's social influence" is a decisive factor for social media INTR 33,2 users to decide whether to spread or stop spreading misinformation, along with other factors such as "the opinion environment" and "the cost to confirm the information."…”
Section: Flow Of Misinformation-related Conversations Through Opinion...supporting
confidence: 73%
“…This four-stage rumor interaction process suggests, like other previous research (e.g. Pang and Ng, 2017), the virality of misinformation can be contingent upon the influences of users on social media platforms. Such importance of communicating actors is further supported by Qin et al (2015, p. 369) who suggest that "the individual's social influence" is a decisive factor for social media INTR 33,2 users to decide whether to spread or stop spreading misinformation, along with other factors such as "the opinion environment" and "the cost to confirm the information."…”
Section: Flow Of Misinformation-related Conversations Through Opinion...supporting
confidence: 73%
“…Meanwhile, concerns over misinformation prevail in the field of digital information and communication (e.g. Cheng and Lee, 2019; Liu and Huang, 2020; Pang and Ng, 2017; Walter and Tukachinsky, 2020). Several scholars conducted research to analyze its diffusion process (Allcott et al , 2019), impact on perceptions of vaccines (Bode and Vraga, 2015) and climate change (Dixon et al , 2017), continued influence of misinformation encountering correction (Walter and Tukachinsky, 2020) and its perceived negative impact on self and others in political elections (Jang and Kim, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Misinformation is incorrect information which can seem to be legitimate initially (Holdeman 2018 ) but can mislead and create harmful effects to the individual and the community (Pang and Ng 2017 ). Love et al ( 2020 ) have identified that misinformation propagation can deepen harmful or deadly effects on people.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, social media is often the source of widespread misinformation (Gupta et al 2013 ; Holdeman 2018 ; Maddock et al 2015 ; Rajdev 2015). Facebook, WhatsApp and Twitter have been identified as social media platforms that spread most misinformation in crises (Nealon 2017 ; Pang and Ng 2017 ).…”
Section: Introductionmentioning
confidence: 99%